Investigating Linguistic Abilities and its Relationship with Empathy, Emotional Intelligence and Cognitive Flexibility - Сударшан Дага; Гаріма Раджан (Психолінгвістика)
Purpose. Languages play an important role in shaping our brain and personality. Numerous studies in the past have found that bilingual and trilingual individuals outperform monolinguals on certain cognitive assessments. In some studies, monolinguals have outperformed the other two groups on emotional tests. Most of the studies have reported mixed findings on this topic, making it difficult to draw conclusions.